2014
DOI: 10.12966/abc.05.08.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nosing Around: Play in Pigs

Abstract: -The predominant method of measuring welfare in swine focuses on overt physical ailments, such as skin lesions, lameness, and body condition. An alternative metric for assessing welfare in swine can be to measure the frequency and duration of positive behavioral states, such as play. Given that play occurs only when an animal's primary needs (food, comfort, safety, etc.) have been satisfied, it has been suggested that play may be a sensitive indicator for assessing the welfare of non-human animals. Play has pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 76 publications
1
36
0
1
Order By: Relevance
“…891). Play in piglets and other juvenile animals is widely considered as a positive welfare marker, which can enhance physical development and create social bonds [54]. It has been suggested that there are several ways that play can be linked to welfare state, play can lead to or cause increased welfare, reduced playfulness can indicate reduced welfare and play can reflect the presence of positive or good welfare [55].…”
Section: Discussionmentioning
confidence: 99%
“…891). Play in piglets and other juvenile animals is widely considered as a positive welfare marker, which can enhance physical development and create social bonds [54]. It has been suggested that there are several ways that play can be linked to welfare state, play can lead to or cause increased welfare, reduced playfulness can indicate reduced welfare and play can reflect the presence of positive or good welfare [55].…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of animal emotions is an important goal in disciplines ranging from neuroscience to animal welfare science, but few reliable tools exist for measuring these emotions [ 4 , 10 ]. Play behaviour is generally recognised as a trigger of positive emotions in mammals [ 30 , 39 ], and previous studies consistently suggested that a high tail movement duration (a behaviour often seen during play) indicates positive emotions in pigs [ 33 35 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this would not explain the overall maintained increase in drinking behavior of IUHS pigs for 7 day post-transport and could indicate that this behavior is not controlled by normal regulatory mechanisms as previously described [44]. One possible explanation for the increase in drinking behavior may be that the IUHS piglets were performing a stereotypic behavior (i.e., polydipsia is a documented stereotypy in pigs [44,45,46,47]) in response to nutrition-related stress. This is because stereotypic behaviors can appear spontaneously in animals that are feed restricted [44], and it has been documented that feed intake is reduced in piglets during the days following weaning and transport [48] due to a rapid shift from an all milk to all solid diet.…”
Section: Discussionmentioning
confidence: 95%